ANALYSIS OF COMPETITIVE IMPROVEMENT OF SOYCULTURE INDUSTRY CLUSTERS IN SUPPORTING FOOD SECURITY IN GROBOGAN DISTRICT USING INDUSTRIAL CLUSTER APPROACH - Ryan Corinus Dato Matheos; Heru Mulyono (Universitas Trisakti, 2018)
Grobogan District in the Province of Center Java, has a potential to produce commodity of horticulture, because of its geography and agroclimate condition that suitable for horticulture plants. The production of horticulture comodities in the Grobogan District can be increased further by doing intensive agriculture and improving farmers' skill. Increasing the productivity and competitiveness of these comodities will support the increasing of import substitution of these comodities in order to save the national foreign exchange income. The objective of this paper is to formulate the strategies based on the industrial cluster and SWOT analysis to increase competitiveness of the horticulture industry sub sector in Grobogan District.